2021
DOI: 10.3389/fpsyt.2021.674460
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Relationship Between Sleep Disorders, Quality of Life and Psychosocial Aspects in Patients With Psoriasis

Abstract: Psoriasis is a chronic, autoimmune skin disease affecting about 2–4% of the worldwide population. It is now perceived as a systemic disease because of the complex pathogenesis and multiple comorbidities. It leads to decreased quality of life and productivity of patients. Nowadays, sleep disorders are investigated as well in relation to psoriasis as another possible comorbidity. This review focuses on possible negative effects of sleep deprivation, decreased quality of life, and psychosocial status in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…Taking into account subjective symptoms related to skin lesions, comorbidities and often time-consuming or cost-effective treatment have a great impact on the decreased quality of life of patients with psoriasis. It was reported that patients with psoriasis are more often absent from work and are less efficient employees, which obviously exacerbate their stress and therefore the disease [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account subjective symptoms related to skin lesions, comorbidities and often time-consuming or cost-effective treatment have a great impact on the decreased quality of life of patients with psoriasis. It was reported that patients with psoriasis are more often absent from work and are less efficient employees, which obviously exacerbate their stress and therefore the disease [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, a recent systematic review [107] having a similar hypothesis concluded that the need for further analysis is critical, since a few unbiased studies could support the positive emotions' effect on sleep in healthy individuals while limited empirical data were not sufficient to provide reasonable evidence for positive emotional outcomes in clinical population. Later studies managed to show that positive affect increased sleep quality [108][109][110], improved self-control, and prevented mood changes [111], in healthy individuals and chronic nonpsychiatric (e.g., thalassemia [112], psoriasis [113]) and psychiatric pathologies [114,115]. By exception, Bouwmans et al [116] reported no correlation between positive affect and sleep quality in depressed patients.…”
Section: The Social Context Of Sleep and Its Relationship With Emotionsmentioning
confidence: 99%
“…Currently, it is increasingly accepted that a good welfare is not merely the lack of negative emotions, but the presence of positive emotions. In this context, from the above discussed studies only Marakkemia et al [113] evaluated and highlighted the possible beneficial effects of encouraging positive emotions.…”
Section: The Social Context Of Sleep and Its Relationship With Emotionsmentioning
confidence: 99%
“…We have also proved that psoriatic patients more often suffer from different sleep disorders [ 11 ]. Moreover, they have been discovered to be less efficient workers or pupils and their life quality is significantly worse than the general population [ 12 ]. Although there are various topical and systemic treatments available for psoriasis, it is often very hard to manage the condition and its multiorgan comorbidities [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the microscopic picture of these two dermatoses is different, sometimes some features may be similar (for instance, the presence of acanthosis) [ 3 , 15 ]. Their pathogenesis is not fully understood, but autoimmune factors are suspected as one of the possible paths, along with drugs, infections, and stress that can trigger the lesions’ occurrence [ 12 , 15 ]. Moreover, both PSO and LP have been related to components of MS [ 6 , 19 ].…”
Section: Introductionmentioning
confidence: 99%